2022
DOI: 10.1039/d2sc00048b
|View full text |Cite
|
Sign up to set email alerts
|

A hypoxia-activated NO donor for the treatment of myocardial hypoxia injury

Abstract: As present NO donor drugs cannot localize to release NO at the hypoxic site, along with the short half-life and bidirectional regulation of NO, they are unable to overcome low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the presence of these dyes, the binding rates of phosphatidylserine on the cell surface are measured with a flow cytometer [35]. In Annexin V–FITC/PI, protocol shows different regions, viable cells (FITC−/PI−), late apoptotic or necrotic cells (FITC+/PI+), and early apoptotic cells (FITC+/PI−) [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of these dyes, the binding rates of phosphatidylserine on the cell surface are measured with a flow cytometer [35]. In Annexin V–FITC/PI, protocol shows different regions, viable cells (FITC−/PI−), late apoptotic or necrotic cells (FITC+/PI+), and early apoptotic cells (FITC+/PI−) [36].…”
Section: Resultsmentioning
confidence: 99%
“…All TLR except TLR3 use myeloid differentiation primary response protein 88 to induce an inflammatory response by activating nuclear factor kappa B (NF-kB) [24][25][26][27][28][29][30][31][32][33][34][35]. Several studies have also reported that TLR pathway activation is also associated with apoptosis of cancer cells through caspase activation [25][26][27][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hypoxia-activated release systems have been investigated for precise hypoxic tumor treatments or hypoxic probe studies so as to promote the effective concentration of pharmacophores in the hypoxic lesion and reduce side effects on normal tissue. Hypoxia stress can cause expression changes of a certain number of genes and related proteins, which could accelerate the release of some pharmacophores. , It has been certified in our previous study that nitroreductase (NTR) is overexpressed in cardiomyocytes under hypoxia, which accelerates intramolecular charge transfer of nitro-aromatics and promotes pharmacophore release by molecular reduction . Therefore, nitro-aromatics can be ideal as hypoxia-activated groups in prodrugs (HAPs) to combine NSAIDs and CAIs, in which they are expected to be activated under hypoxia to release corresponding pharmacophores and present desirable therapeutic effects and safety for treating cardiac diseases associated with hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 It has been certified in our previous study that nitroreductase (NTR) is overexpressed in cardiomyocytes under hypoxia, which accelerates intramolecular charge transfer of nitro-aromatics and promotes pharmacophore release by molecular reduction. 22 Therefore, nitro-aromatics can be ideal as hypoxia-activated groups in prodrugs (HAPs) to combine NSAIDs and CAIs, in which they are expected to be activated under hypoxia to release corresponding pharmacophores and present desirable therapeutic effects and safety for treating cardiac diseases associated with hypoxia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PDT, which employs light-excited photosensitizer to react with surroundings oxygen to generate highly active singlet oxygen, is the most commonly used ROS-based treatment approach. PDT has good selectivity and minimal trauma, overcoming some disadvantages of traditional therapies. , The therapeutic effect of PDT largely depends on the environmental oxygen concentration. However, most solid tumors have the problem of uneven oxygen distribution due to abnormal angiogenesis. , In the superficial area of tumor, sufficient blood flow can maintain the oxygen concentration at normal level; while in the internal region of tumor, insufficient oxygen supply will lead to the emergence of hypoxic region. Limited by the heterogeneity of the tumor oxygen environment, PDT is difficult to achieve a satisfactory therapeutic effect. In the past several years, some alternative dynamic therapies that can generate ROS or free radicals in an oxygen-independent manner have been developed.…”
mentioning
confidence: 99%